THE IMPORTANCE OF EARLY CARDIOVERSION OF PAROXYSMAL ATRIAL FIBRILLATION - Franc Verovnik (Zdravniški Vestnik, 2002)
Background. Atrial fibrillation is one of the most common arrhythmias. There is a traditional division by time course into acute and chronic forms. The classification of acute forms is unsatisfactory. Paroxysmal atrial fibrillation is one of the acute forms. There is a great variation in the frequency, duration and clinical pictures of its episodes. These can be asymptomatic or may cause significant hemodynamic disturbances, more or less unpleasant for the patients. There is growing evidence that paroxysmal atrial fibrillation could confer a hypercoagulable state, which is well known for the chronic atrial fibrillation. The possibility of thromboembolic incidents increases with the duration of an episode of paroxysmal atrial fibrillation and is dependent on risk factors for thromboembolisms. Conclusions. The early cardioversion of paroxysmal atrial fibrillation into sinus rhythm is indicated when significant hemodynamic disturbances are present. Pharmacological or electrical cardioversion could be used. The early cardioversion is also recommended, as the possibility of thromboembolic incidents in the first few hours is very low.There are no firm guidelines for profilactic anticoagulation during an attack of paroxysmal atrial fibrillation. The decision for permanent antithrombotic therapy of patients with paroxysmal atrial fibrillation is based on duration and frequency of episodes, on patient’s age, and risk factors for thromboembolisms in atrial fibrillation.